Effects of ultrasonic treatment on the cooking and fermentation properties of Shanlan rice. (September 2020) - Yang, Zixuan; Lin, Xue; Wang, Lu; Li, Congfa; Liu, Sixin
Abstract: Shanlan rice is an endemic upland rice in Hainan province, China. In this study, we investigated the effects of ultrasonic treatment (UT) on the cooking and fermentation properties of Shanlan rice. These effects were evaluated by multiple physical and chemical indicators via scanning electron microscopy (SEM), low-field nuclear magnetic resonance (LF-NMR), and high-performance liquid chromatography (HPLC). According to the minimal cooking time and the content of total leached solids, the optimal ultrasonic power and time were determined to be 240 W and 30 min, respectively. The results indicated that the ultrasonic treatment broke the rice surface, loosened the inner structure of rice, and extended the relaxation time. These changes increased water absorption during the cooking process by 8.2% and promoted saccharification and alcohol production at the initial fermentation stage, with a 54.1% higher alcohol content on the first day. The rice wine brewed from the treated rice showed differences in the non-volatile acid contents; malic acid and tartaric acid contents increased, while the acetic acid content decreased significantly. Moreover, the red colour and brightness of the rice wine were significantly improved after the ultrasonic treatment, with a 16.6% increase in the rice wine yield. Graphical abstract: Image 1 Highlights: Ultrasonic treatment changed the microstructure and proton statue of Shanlan rice. Ultrasonic treatment improved partial cooking and fermentation performance of Shanlan rice. Ultrasonic treatment influenced several properties of Shanlan rice wine.